Library and the New Normal in Thailand - Pluemsamrungit, Preedee; Sukanya, Pongsakorn (Reading Journal, 2021)
The New Normal caused from spreading of the Covid-19 makes the livelihood of people changed. The adaptation and changing daily-life behaviors needed to get through this crisis. The libraries have adapted and modified their work processes to provide service and support continuously. This article is to explore adaptation of the library services in the COVID-19 pandemic situation to support users’ information access and information literacy.